Parent-adolescent relationship quality as a predictor of leaving home. (February 2020) - Akın, Rengin Işık; Breeman, Linda D.; Meeus, Wim; Branje, Susan
Abstract: Introduction: Leaving home is a significant life transition that effects both emerging adults and their families. The age of leaving home has been increasing across industrialized societies, and children remain dependent on their parents for a longer time. The present study investigated the association between parent-adolescent relationships and timing of leaving home over a timespan of six years: From middle adolescence to emerging adulthood. Methods: Data came from three cohorts of two longitudinal studies in the Netherlands (N = 1100). At the start of the study, participants had a mean age of 16.41 ( SD= .71), and approximately half of them ( n  = 547) were male. Adolescents completed questionnaires on parent-adolescent relationship quality. The impact of positive and negative relationship characteristics on timing of leaving home were examined separately for mothers and fathers. Results: Survival analysis results showed that higher levels of mother's and father's warmth, and higher levels of power attributed to father, but not mother, predicted later timing of leaving home. Higher levels of parental autonomy support predicted earlier timing of leaving home. Conflict with parents was not associated with timing of leaving home, except in the father-daughter relationship. Only, the effect of parental warmth on timing of leaving home remained robust when controlling for age, gender, education level, and SES. Conclusions: Our findings indicate that certain parent-adolescent relationship characteristics contribute to the increase in age of leaving home. Parents may be able to prepare their children for a self-sufficient living by balancing warmth and autonomy support they provide during adolescence.